Money and the Scale of Cooperation - Maria Bigoni; Gabriele Camera; Marco Casari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This study reveals the existence of a causal link between the availability of money and an expanded scale of interaction. We constructed an experiment where participants chose the group size, either a low-value partnership or a high-value group of strangers, and then faced an intertemporal cooperative task. Theoretically, a monetary system was inessential to achieve cooperation. Empirically, without a working monetary system, participants were reluctant to expand the scale of interaction; and when they did, they ended up destroying surplus compared to partnerships, because cooperation collapsed in large groups. This economic failure was reversed only when participants managed to concurrently develop a stable monetary system.
Keywords: C70; C90; D80; 330